The rights and best interests of children conceived through rape: the missing maintenance of rapist fathers in South Africa - Friedmann, Indio Anais (Department of Public Law, 2025)
The global shift in recognising children as independent rights holders demands that States Parties must adhere to the best interests of the child principle, obliging them to adopt legislative measures that align with children's rights as outlined in international law. Accordingly, South Africa's legislative frameworks, including the Children's Act 38 of 2005, emphasise a child centered approach, requiring all child-related decisions to be grounded in the best interests of the child. However, there is a notable absence in international and domestic guidance regarding the rights and best interests of children conceived through rape. It is within this context that this dissertation argues that South Africa's current legislation fails to adequately provide for children born of rape. Such a failure violates international and constitutional obligations owed to children. This dissertation examines this current legislative lacuna in South Africa concerning such children, specifically focusing on the Children's Act and Maintenance Act 99 of 1998. The Children's Act, in section 1(a), excludes rapist fathers from the definition of a parent, thereby denying them parental responsibilities and rights, including the responsibility to contribute to the child's maintenance. While seemingly aimed at protecting the child's best interests, this legal stance creates a lacuna, leaving children born of rape without maintenance from the rapist father. Maintenance is a crucial factor determining a child's well-being and opportunities, encompassing rights such as adequate living standards, education, healthcare, housing, and dignity. The existing legislation only entitles children born of rape to maintenance from the biological mother, unlike children born of consent who can receive dual maintenance. Moreover, this differential treatment based on the manner of conception raises concerns of unfair discrimination. Due to these consequences, amendments to the Children's Act and Maintenance Act are necessary to ensure maintenance obligations from rapist fathers, irrespective of the child's birth status. By analysing international and domestic perspectives, this research highlights the child's right to receive maintenance as part of their best interests, challenging the current exclusionary provision in its current form.